SEXUAL BEHAVIOUR AS AN INDEX OF FERTILITY IN BARBARI GOATS - BARIK, A K; VERMA, R P; SINGH, L P; KUMAR, SATISH; VARSHEN, V P; ANSARI, M R; PATTANAIK, A K (The Indian Journal of Animal Reproduction, 2023)
Six juvenile bucks of 12 months of age were studied for sexual behaviour at the time of semen collection. Various parameters like sexual behaviour, reaction time, tactile stimulation and mating ability were studied. The sexual behaviour ranged from 71.50 to 93.66 per cent which was significantlycorrelated (-0.895) with reaction time. The reaction time ranged from 17.08 to 24.00 seconds. The differences between the sexual behaviour and reaction time between the bucks were statisticallysignificant.
Keywords: Sexual behaviour; Fertility; Goats